Initiation of an Explosive Charge by Consecutive Projectiles - Partom, Yehuda (European Journal of Applied Sciences, 2022)
Test results reported in [1,2] show that when two consecutive projectiles hit an explosive charge, and when their velocity is such that the first projectile is just below the initiation threshold, the second projectile is able to initiate the explosive. We propose here an explanation to this important phenomenon. Our explanation is based on our reactive flow model TDRR for which the explosive reaction rate increases with the reactant temperature. We use our reactive flow code to demonstrate how this works. To simplify the computations, we hit the explosive charge with two consecutive pressure pulses instead of with two projectiles.